Rethinking Ḥadīth (Prophetic Traditions) as ‘Natural’ Narrative: In the Framework of Fludernik’s ‘Natural’ Narratology - Fatma Yüksel Çamur (Ankara Üniversitesi İlahiyat Fakültesi Dergisi)
Bythe concept of ‘natural’ narrative, Monika Fludernik brought a new perspectivefor narratology in the late ’90s. In her narrative theory, narrativity startswith the human experience rather than the plot. Fludernik’s approach mayprovide an insight into understanding ḥadīth. Each ḥadīth accountis a report of a saying, an event, or an experience about the Prophet Muhammadfrom the perspective of companion narrators. Ḥadīth also asserts theProphet’s life experience by telling how he acted in his life and reacted topeople’s attitudes. Ḥadīth transmission is also an experience referringto narration of prophetic knowledge from one generation to the next. In thisarticle, I try to discuss to what extent ḥadīth can be considered‘natural’ narrative in the framework of Fludernik’s theory.